Implementasi Manajemen Sarana dan Prasarana di SMK Ma'arif 9 Kebumen - Aprilia Anggin Cahyani; Imam Subarkah (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The objectives of this study are: (1) to determine the implementation of facilities and infrastructure management at SMK Ma'arif 9 Kebumen (2) to determine the condition of facilities and infrastructure at SMK Ma'arif 9 Kebumen (3) to determine the management of facilities and infrastructure at SMK Ma'arif 9 Kebumen is / is not in accordance with the guidelines for facilities and infrastructure management. not in accordance with the facilities and infrastructure management guidelines. This research uses qualitative research methods, in which researchers make observations to the field to find out phenomena or facts. The subjects in this study were the principal, the head of facilities and infrastructure, and the administrative staff. Data collection techniques are interviews, observation, and documentation. Data analysis used is data reduction, data presentation, and conclusion drawing. Based on the research results, it can be concluded that: (1) the implementation of facilities and infrastructure management at SMK Ma'arif 9 Kebumen is carried out by planning, procurement, inventory, distribution, maintenance, storage, and elimination (2) the condition of facilities and infrastructure at SMK Ma'arif 9 Kebumen is quite adequate, although there is still a shortage of classrooms due to the increasing number of students every year (3) the management of facilities and infrastructure at SMK Ma'arif 9 Kebumen is in accordance with the facilities and infrastructure management guidelines.